TEACHING CREATIVE ACTIVITY OF SINGING IN MUSIC EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In the process of learning to sing a song to children, it is necessary to perform a number of activities before and during the singing of a certain song. To form initial impressions about the song. You will have information about the importance of the correct implementation of the method of re-singing exercises in the formation of singing skills.